1992
DOI: 10.1093/protein/5.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a 16 kDa integral membrane protein that has identity to the putative proton channel of the vacuolar H+-ATPase

Abstract: A 16 kDa protein has been isolated in a homogeneous form as the major component of a paracrystalline paired membrane structure closely resembling the gap junction. The primary structure of this protein from arthropod and vertebrate species has been determined by protein and cDNA sequencing. The amino acid sequences are highly conserved and virtually identical to the amino acid sequence of the proteolipid subunit of the vacuolar H(+)-ATPases. The disposition of the protein in the membrane has been studied using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 0 publications
7
56
0
Order By: Relevance
“…However, the arrangement of the major subunit (subunit c) of the membrane sector, V o , is known. This is as a result of the unexpected finding that subunit c is the sole protein component of another membrane complex found in metazoans, the connexon channel of gap junction structures [7], which was first imaged 20 years ago [8,9].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the arrangement of the major subunit (subunit c) of the membrane sector, V o , is known. This is as a result of the unexpected finding that subunit c is the sole protein component of another membrane complex found in metazoans, the connexon channel of gap junction structures [7], which was first imaged 20 years ago [8,9].…”
Section: Overviewmentioning
confidence: 99%
“…If Vma8p (perhaps in conjunction with Vma4p) is a homologue of the γ subunit of the F 1 -ATPase, it would by analogy be central to V 1 . Vma7p (7) has been proposed to be functionally analogous to the ε subunit of the F-ATPase, and appears also to be part of a ' core ' V 1 complex. The Vma5p subunit (5), although essential for coupling of V 1 to V o , does not appear to be a crucial component in the assembly of V 1 , and the reconstituted enzyme is active even in the absence of this subunit.…”
Section: Figure 1 Structural Model Of the Saccharomyces V-atpasementioning
confidence: 99%
See 1 more Smart Citation
“…The 16-kDa proteolipid subunit of the vacuolar ATPase, known as ductin (Finbow et al, 1992), has also been suggested to be able to form functional gap junctions between cells (Finbow and Pitts, 1993). Because of the important physiological and regulatory roles for this subunit, we examined its expression pattern in both chick and frog embryogenesis.…”
Section: K(v)lqt-1 (Kcnq1)mentioning
confidence: 99%
“…The 16-kDa protein belongs to a family of proteins with quite diverse functions ranging from proton pumping activity and cellular communication to the release of acetylcholine in response to elevated Ca 2+ levels and cellular transformation processes [15][16][17][18]. Electron microscopical data of the first 2-D crystals grown from solubilised 16-kDa protein are presented, and it is suggested that this novel approach may be a valuable tool for the 2-D crystallisation and structural elucidation of a wide range of membrane proteins.…”
Section: Introductionmentioning
confidence: 99%